y=\frac{1}{4}\cdot x + 3
|
y=\frac{-5}{4}\cdot x + 4
|
y=\frac{-5}{4}\cdot x + 1
|
y=\frac{3}{2}\cdot x + 2
|
y=\frac{1}{4}\cdot x + 2
|
y=\frac{-3}{4}\cdot x + 1
|
y=\frac{5}{2}\cdot x + 4
|
y=\frac{-3}{4}\cdot x + 4
|
y=\frac{3}{2}\cdot x + 3
|
y=\frac{3}{2}\cdot x + 1
|
y=\frac{1}{2}\cdot x + 1
|
y=\frac{-3}{2}\cdot x + 4
|
y=\frac{-3}{2}\cdot x + 1
|
y=\frac{-1}{2}\cdot x + 1
|
y=\frac{-5}{2}\cdot x + 1
|
y=\frac{5}{4}\cdot x + 1
|
y=\frac{5}{4}\cdot x + 1
|
y=\frac{1}{4}\cdot x + 4
|
y=\frac{5}{2}\cdot x + 1
|
y=\frac{-1}{2}\cdot x + 3
|
y=\frac{3}{2}\cdot x + 4
|
y=\frac{-5}{2}\cdot x + 2
|
y=\frac{-3}{2}\cdot x + 4
|
y=\frac{5}{4}\cdot x + 1
|